Impact of AOD and Parental Income on the Academic Performance of Students - Dr. Dipti Sethi1, Binit2 (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
In today's academic landscape, students’ academic performance serves as a crucial yardstick for success. This research endeavors to ascertain whether decision-related action orientation (AOD) and parental income can be considered predictors of students' academic performance. The study aims to establish the correlation between Action versus State Orientation, parental income, and students' academic performance. The research utilized a quantitative survey instrument to collect data. The results indicate that AOD significantly affects students' academic performance, whereas parental income does not. The study concludes by underscoring the implications of these results for educators and suggesting potential avenues for future research.